CARBON FOREST PROJECTS IN THE CONTEXT OF ENVIRONMENTAL MANAGEMENT EFFICIENCY - Alla Pakina (Zbornik Radova: Geografski institut "Jovan Cvijić")
Carbon Forests Projects (CFPs) play a significant role in climate change mitigation strategies. Implementation of such projects should bring environmental benefits to companies, as well as contribute to improving the environmental management efficiency in the region. The aim of this paper is to analyze the possibility of developing CFPs as a tool to achieve carbon neutrality, taking into account its environmental and economic benefits. The analysis is undertaken on the example of the Bystrinsky Mining and Processing Plant (MPP), located at the Zabaykalsky Krai (southern Siberia, Russia). The ability of the forest lands to absorb greenhouse gas emissions is assessed using the ROBUL methodology. An important feature of CFPs is the ability to combine a positive environmental effect by contributing to climate change mitigation with strengthening the image of an environmentally friendly company. However, the analysis of CFPs implementation in the example of Bystrinsky MPP shows the excess of costs over benefits. In this regard, more effective projects can be proposed for regions with a high degree of forest cover, such as Zabaikalie. Reducing the risk of forest fires in such regions can have a more tangible environmental impact by preventing additional CO2 emissions. Identifying and comprehensively assessing the environmental and economic impacts of CFPs in the context of carbon neutrality facilitates the selection of the most relevant solutions.